Construction of a physical-mechanical model of reinforcing microrelief formation on profiled strips made of AISI 1005 and AISI 347 steels considering surface topology - Kyrychok, Petro; Paliukh, Dmytro (Eastern-European Journal of Enterprise Technologies, 2025)
This study’s object is the process that forms a strengthening microrelief on the surface of profiled folding plates made of AISI 1005 and AISI 347 steels through localized indentation using a spherical indenter made of a diamond-based composite material. The principal hypothesis of the study posits that the implementation of a controlled surface texturing process enables the formation of a stable microrelief with predefined geometric characteristics. Achieving this requires establishing the regularities of microrelief formation depending on the physical and mechanical properties of the material, the geometry of the indenter, and the parameters of the contact interaction. A physical and mechanical model of the contact interaction between the indenter and the metallic plate has been built. The results of the analytical modeling were validated through profilometric measurements and 3D visualizations, which revealed differences in the depth and nature of deformation between AISI 1005 and AISI 347. The AISI 1005 steel exhibited higher plasticity and a greater tendency toward deep deformation, whereas AISI 347 demonstrated superior stability in the relief geometry. An evaluation of surface roughness parameters (Ra, Rz, Rmax) indicated that the AISI 347 steel provides better reproducibility of the strengthening effect, with average Ra and Rz values being 2–2.5 times lower than those of AISI 1005. The correlation analysis of microrelief parameters revealed a strong relationship between Ra and Rz values, with a correlation coefficient ranging from 0.93 to 0.96. This finding confirms the stability of the microrelief formation mechanism and justifies the use of AISI 347 steel in combination with a Ø3.5 mm indenter. The results of this study can be applied for manufacturing folding elements with enhanced wear resistance and geometric stability under cyclic loading conditions